El reconocimiento del tercer sector de la economía y su afectación en la falta de ordenamiento jurídico. - TAPIA MURIEL, CLEVER JORGE (2012)
Among the new policies proposed by the present Constitution, adopted and signed in Montecristi in 2008. It is recognized within the financial system to a third component is the popular finance sector and Solidarity (FPS) which has been working and to leverage other sectors of the economy (public and private sector). The existing constitutional rules formalize the existence of this sector for years forgotten and marginalized, but only via your items while all government support, social and political development is stalled pending a legal and operational standards to institutionalize this ambitious goal. In this paper we review statistical data specifically concerning the lack of legal and institutional framework is crippling a nation's social proposal that disadvantaged economic sectors. It gives the nation a turning point that must be understood in all its dimensions understanding and accepting that the only possible way to live in harmony is ensuring Kausay Sum (good life) through a better allocation of resources to enable the economically active initiatives and manage to produce so as to sustain a more just and equitable society, breaking the traditional models of class struggle and total exclusion. As university students we have a moral commitment to our society, who must shape generating new governance options covered in the ethics, morality and entrepreneurship, factors that allow us to reach new political currents of governance for the benefit of the majority for years neglected and marginalized.